Small Molecule-Peptide Conjugates as Dimerization Inhibitors of Leishmania infantum Trypanothione Disulfide Reductase - Alejandro Revuelto; Isabel López-Martín; Héctor de Lucio; Juan Carlos García-Soriano; Nicola Zanda; Sonia de Castro; Federico Gago; Antonio Jiménez-Ruiz; Sonsoles Velázquez; María-José Camarasa (MDPI AG, 2021)
Trypanothione disulfide reductase (TryR) is an essential homodimeric enzyme of trypanosomatid parasites that has been validated as a drug target to fight human infections. Using peptides and peptidomimetics, we previously obtained proof of concept that disrupting protein-protein interactions at the dimer interface of Leishmania infantum TryR (LiTryR) offered an innovative and so far unexploited opportunity for the development of novel antileishmanial agents. Now, we show that linking our previous peptide prototype TRL38 to selected hydrophobic moieties provides a novel series of small-molecule-peptide conjugates that behave as good inhibitors of both LiTryR activity and dimerization.